Creation of multiple NV centers by phthalocyanine ion implantation. (1st June 2022) - Kimura, Kosuke; Onoda, Shinobu; Yamada, Keisuke; Kada, Wataru; Teraji, Tokuyuki; Isoya, Junichi; Hanaizumi, Osamu; Ohshima, Takeshi
Abstract: A nitrogen vacancy (NV) center in diamond is known as a solid-state spin qubit at room temperature. NV centers coherently coupled by dipole–dipole interactions have a potential to accomplish quantum registers at room temperature. This study reports to develop a phthalocyanine ion implantation technique to fabricate multiple dipole-coupled NV centers. Photon counts and optically detected magnetic resonance spectra show that up to four NV centers were successfully created in a confocal spot. The histogram of photon counts is fitted by a Poisson distribution, and the ratio of multiple NV spots suggests the potential for a five NV centers creation.